2020
DOI: 10.3390/cells9051114
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Treatment Results in GLUT4 Translocation and AMPK Phosphorylation in Neuronal SH-SY5Y Cells

Abstract: Interleukin-6 (IL-6) is a pleiotropic cytokine that can be released from the brain during prolonged exercise. In peripheral tissues, exercise induced IL-6 can result in GLUT4 translocation and increased glucose uptake through AMPK activation. GLUT4 is expressed in the brain and can be recruited to axonal plasma membranes with neuronal activity through AMPK activation. The aim of this study is to examine if IL-6 treatment: (1) results in AMPK activation in neuronal cells, (2) increases the activation of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
(99 reference statements)
0
16
0
Order By: Relevance
“… 30 IL-6 may influence expression of Glut4, Irs1 , and Ampk , which regulate lipid and glucose metabolism. 31 TNF-α can also downregulate the expression of PGC1α, PDK4, and CPT1, which play critical roles in regulating energy metabolism. 32 Elevated levels of circulating pro-inflammatory cytokines also indicate poor prognosis in patients with heart failure because activation of immune response in the heart leads to adverse cardiac remodeling and left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“… 30 IL-6 may influence expression of Glut4, Irs1 , and Ampk , which regulate lipid and glucose metabolism. 31 TNF-α can also downregulate the expression of PGC1α, PDK4, and CPT1, which play critical roles in regulating energy metabolism. 32 Elevated levels of circulating pro-inflammatory cytokines also indicate poor prognosis in patients with heart failure because activation of immune response in the heart leads to adverse cardiac remodeling and left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…The changes at protein level of HXK-2 and GCK in the hypothalamus of the STZ-treated rats predispose to enhanced glucose phosphorylation [ 55 ], while the elevated level of GLUT4 suggests that not only insulin signalling but miRNAs affected protein synthesis is also important in the expression of GLUT4 and glucose uptake. Moreover, the elevated level of inflammatory cytokines such as IL-6 can contribute to the increased GLUT4 level independently of insulin [ 56 ]. On the other hand, the raising protein level of LEPR may trigger the effect of leptin on lowering glucose concentration in the circulation [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMPK, a sensor of glucose limitations and cellular energy status [39,40], is activated to resolve nutrient resource-need imbalances and is critical for diabetes and cancer development. IL-6 acts on glucose metabolism [41] and AMPK activation to promote GLUT4 translocation to the neuronal plasma membrane [42], resulting in enhanced glucose uptake in neuronal cells. Relevant to the inhibition of the IL-6/p-AMPK axis by combined olaparib and Oligo-Fucoidan treatment, we found that not only glucose metabolism factors, such as glucose transporter-1 (Glut1), phosphofructokinase (PFKL), ribose 5-phosphate isomerase A (RPIA) and phosphorpyruvate kinase 2 (p-PKM2) (Tyr105) (Fig.…”
Section: Combining Olaparib and Oligo-fucoidan Treatment Of Tnbc Cell...mentioning
confidence: 99%